Clinical and Complement Long-Term Follow-Up of a Pediatric Patient with C3 Mutation-Related Atypical Hemolytic Uremic Syndrome - Anna Bjerre; Grethe Bergseth; Judith Krey Ludviksen; Arne Stokke; Vidar Bosnes; Diana Karpman; Tom Eirik Mollnes (Case Reports in Nephrology)
We report a pediatric patient with atypical hemolytic uremic syndrome due to a C3 gain-of-function mutation diagnosed in infancy. She was treated from the start with a constant dose of 300 mg eculizumab every second week from the onset and followed by routine complement analyses for six years. Her complement system was completely inhibited and the dose interval was prolonged from 2 to 3 weeks without alteration of the dose and the complement activity continued to be completely inhibited. Blood samples taken immediately before, immediately after, and between eculizumab doses were analyzed for eculizumab-C5 complexes and percentage of total complement activity, using the Wieslab® test, and compared to a pool of sera from 20 healthy controls. The patient exhibited complete complement inhibition at all three time-points and had no free circulating C5 suggesting there was complete binding to eculizumab. She has now been treated for six years with full complement blockade. We suggest therefore that analysis of complement activity using the Wieslab® test is useful for evaluating the effect of eculizumab when dose intervals are prolonged.